(untitled) (Revista de Ciências Agroveterinárias, 2014)
Information on the reproductive biology of species are key to planning land use guides and the conservation of forest resources. Thus, aspects of fl oral biology and breeding systems, flower visitors and the fruit development of Ilex paraguariensis A. St. Hil. were studied in an area of Mixed Ombrophylous Forest (Fazenda das Nascentes) in the city of Urupema, Santa Catarina state. For this study we monitored 161 individual adult erva mate (86 male and 75 female) plants during the period August 2011 to May 2012. The reproductive phenology showed 100 days, with peak flowering in the month of November and beginning of fruit ripening in May. The flowering of this species was recorded during periods of reduced precipitation and with an average temperature above 25°C. The flower visitors belonging to the orders Hymenoptera, Coleoptera, Hemiptera and Diptera visited the flowers during the day, during the period from 08:30 AM to 06:00 PM. The development of the fresh weight of the fruit increased quadratically. The results indicate the need for monitoring of reproductive individuals for a longer time which will allow more complete understanding of the reproductive cycle of erva mate in order to subsidize conservation strategies and management of this resource in the forest formations of Catarinense Highlands.